Diffuse histology-proven mucinous cystic neoplasm of the pancreas: A case report and review of literature. (2019) - Nicolas, Clara T.; Al Diffalha, Sameer; Reddy, Sushanth
Highlights: MCN is very rarely multicentric. Presence of ovarian-type stroma is required for the diagnosis of MCN. This is a case of diffuse MCN in the setting of chronic pancreatitis. It highlights the importance of multidisciplinary care for pancreatic cystic disease. Abstract: Introduction: Mucinous cystic neoplasms (MCN) are rare premalignant neoplasms of the pancreas that are typically found as single lesions in the pancreatic body and tail of women in the fifth and sixth decade of life, do not communicate with the pancreatic ductal system and are characterized by mucin-producing epithelium supported by ovarian-type stroma. Presentation of case: We present here a case of diffuse pancreatic involvement by MCN in a 64-year-old woman with chronic pancreatitis. Pre-operative suspicion for MCN was low due to the multi-centric nature of the lesions and imaging/biochemical fluid analysis demonstrating connection with the pancreatic ductal architecture. The patient underwent total pancreatectomy with pathology showing multiple cysts lined by flat epithelium with focal ovarian-type stroma, consistent with low-grade MCN. Discussion: The presence of ovarian stroma on histological analysis is one of the defining characteristics of MCNs per WHO guidelines, and is mandatory for its diagnosis. Only one case of diffuse MCN has been previously described in the literature; however, in this case the authors were not able to reach a definitive histological diagnosis based on WHO criteria. Conclusion: To our knowledge, this is the first report of diffuse histology-proven MCN of the pancreas.